Open Science, Publications and Code - Harrison, Melissa (OpenEdition Press, 2022)
I am a publisher and have been a publisher for most of my career, including working at eLife. I now work at EMBL-EBI managing an open access repository. We have over 7.5 million full‑text articles and preprints, the COVID‑19 preprint subset and some others. The perspectives I have gained from those two different roles are interesting. From the perspective of an open access publisher, one of the problems that we encountered at eLife when trying to encourage responsible behaviours such as the use...